Utilizing Andrographis paniculata leaves and roots by effective usage of the bioactive andrographolide and its nanodelivery: investigation of antikindling and antioxidant activities through in silico and in vivo studies - Baru Venkata, Ramana; Prasanth, Dintakurthi Sree Naga Bala Krishna; Pasala, Praveen Kumar; Panda, Siva Prasad; Tatipamula, Vinay Bharadwaj; Mulukuri, Sirisha; Kota, Ravi Kumar; Rudrapal, Mithun; Khan, Johra; Aldosari, Sahar; Alshehri, Bader; Banawas, Saeed; et al. (Frontiers in Nutrition, 2023)
To valorise the bioactive constituents abundant in leaves and other parts of medicinal plants with the objective to minimize the plant-based wastes, this study was undertaken. The main bioactive constituent of Andrographis paniculata, an Asian medicinal plant, is andrographolide (AG, a diterpenoid), which has shown promising results in the treatment of neurodegenerative illnesses. Continuous electrical activity in the brain is a hallmark of the neurological conditions such as epilepsy. In this study, we used GSE28674 as a microarray expression profiling dataset to identify DEGs associated with andrographolide and those with fold changes >1 and P-value< 0.05 GEO2R. We obtained eight DEG datasets (two up and six down). There was marked enrichment under various Kyoto Encyclopaedia of Genes and Genomes (KEGG) and Gene Ontology (GO) terms for these DEGs (DUSP10, FN1, AR, PRKCE, CA12, RBP4, GABRG2, and GABRA2). The low bioavailability of AG is a significant limitation of its application. To control these limitations, andrographolide nanoparticles (AGNPs) were prepared and their neuroprotective effect against pentylenetetrazol (PTZ)-induced kindling epilepsy was investigated using network pharmacology (NP) and docking studies to evaluate the antiepileptic multi-target mechanisms of AG. Andrographolide is associated with eight targets in the treatment of epilepsy. Nicotine addiction, GABAergic synapse, and morphine addiction were mainly related to epilepsy, according to KEGG pathway enrichment analysis (P <0.05). A docking study showed that andrographolide interacted with the key targets. AG regulates epilepsy and exerts its therapeutic effects by stimulating GABA production. Rats received 80 mg/kg body weight of AG and AGNP, phenytoin and PTZ (30 mg/kg i.p. injection on alternate days), brain MDA, SOD, GSH, GABAand histological changes of hippocampus and cortex were observed. PTZ injected rats showed significantly (***P<0.001) increased kindling behaviour, increased MDA, decreased GSH, SOD, GABA activities, compared with normal rats, while treatment AGNPs significantly reduced kindling score and reversed oxidative damage. Finally, we conclude that the leaves and roots of A. Paniculata can be effectively utilized for its major bioactive constituent, andrographolide as a potent anti-epileptic agent. Furthermore, the findings of novel nanotherapeutic approach claim that nano-andrographolide can be successfully in the management of kindling seizures and neurodegenerative disorders.